2013
DOI: 10.1007/s11307-013-0677-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Molecular Imaging of Apoptosisand Necrosis in Atherosclerotic PlaquesUsing MicroSPECT-CT and MicroPET-CT Imaging

Abstract: Both (99m)Tc-AnxAF568 and (124)I-Hyp uptake are increased in atherosclerotic carotid vasculature compared to control arteries. While apoptosis imaging remains challenging, necrosis imaging can be feasible after improving the biodistribution characteristics of the probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The peptide is extensively cross-linked by intramolecular covalent bridges that provide relatively high in vivo stability. The agent has targeting activities comparable to 99m Tc-annexin-V, which binds to the negatively charged PS in the presence of Ca 2+ [9, 40-44], but unlike annexin-V it has peptide-like pharmacokinetics [45]. The combination of these factors makes 99m Tc-duramycin potentially a more attractive atherosclerosis imaging agent than 99m Tc-annexin-V, which has a low target-to-background ratio and high uptake in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide is extensively cross-linked by intramolecular covalent bridges that provide relatively high in vivo stability. The agent has targeting activities comparable to 99m Tc-annexin-V, which binds to the negatively charged PS in the presence of Ca 2+ [9, 40-44], but unlike annexin-V it has peptide-like pharmacokinetics [45]. The combination of these factors makes 99m Tc-duramycin potentially a more attractive atherosclerosis imaging agent than 99m Tc-annexin-V, which has a low target-to-background ratio and high uptake in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, defective efferocytosis and ensuing cell death of macrophages and smooth muscle cells (SMCs) promote plaque necrosis and instability [6]. A necrotic core is a prominent feature of advanced plaques [7-9]. Necrotic macrophages release cytoplasmic content and further induce enhanced inflammation and plaque instability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore annexin V, a protein that binds to PS, has been labeled with radionuclides ( 123 I, 124 I, 99m Tc and 18 F) [103] to detect apoptosis. A combination of annexin 5 labeled with 99m Tc for SPECT imaging of apoptosis and together with hyper-icin labeled with 124 I for PET imaging of necrosis was used to image plaques in apoE −/− mice [104]. Imaging of apoptotic cells in atheroma may demarcate plaques at risk for future complications [105].…”
Section: Molecular Imaging and Atheroslerosis Detectionmentioning
confidence: 99%
“…As for the PET/ SPECT probes including 18 F-ML-10, 2-(5-fluoro-pentyl)-2-methylmalonic acid targeting apoptosis-specific membrane alterations [18] and 18 F-isatin derivatives targeting caspase-3 [17] have been evaluated. On the other hand, considering the fact that acellular necrotic cores are more abundant in advanced lesions, De Saint-Hubert et al evaluated the potential of 124 I-Hypericin for imaging atherosclerotic plaques [50]. Consequently, they indicated that necrosis imaging can be feasible, although the pharmacokinetic characteristics of 124 I-Hypericin should be improved.…”
Section: Pet/spect Probes For Imaging Targets Other Than Inflammatorymentioning
confidence: 99%